Laser ablation and two-step photo-ionization for the generation of 40Ca+. (19th September 2018) - Shao, H; Wang, M; Zeng, M; Guan, H; Gao, K
Abstract: In this paper, we present a detailed method for rapidly and effectively loading a single 40 Ca + ion into a miniature linear Paul trap. Calcium atoms are generated by laser ablation, and the single ion is loaded and specific isotopes are selected by a two-step photo-ionization method. Compared to the traditional photo-ionization method in which atoms are typically emitted from a resistively heated oven, the advantages of laser ablation are that it can be precisely controlled, it can effectively avoid the problem of fluxed calcium deposition on the trap electrodes, and it restricts the generation of dark ions, which can influence atomic-precision spectroscopy measurements. With its short loading time, it is possible to load an ion in few seconds with the appropriate parameters. The technique of laser ablation has been applied to generate several species of atoms and ions at present, it will potentially benefit in the studies of optical frequency standards, quantum simulation and quantum information processing in an ultra-high vacuum condition and cryogenic system.